2013
DOI: 10.1177/001440291307900402
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Students with Significant Cognitive Disabilities on Early-Grade Curriculum-Based Measures of Word and Passage Reading Fluency

Abstract: Alternate assessments have been used for the last 10 years to evaluate schools' efforts to teach children with significant cognitive disabilities. However, few studies have examined the reading skills of children who participate in these assessments. The purpose of this study was to extend understanding of the reading skills of this population by administering early-grade word and passage reading fluency curriculum-based measures to a sample of 7,440 students in Grades 3 through 8 and 11. Overall, the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
1
38
1
Order By: Relevance
“…Despite their achievements in word reading and comprehension (Jones et al, 2006;Lemons et al, 2013), most individuals with ID struggle to read and comprehend sentences (Fajardo, Ávila, Ferrer, Tavares, Gómez, & Hernández, 2014). Recently, van Wingerden et al (2016) evaluated the development of sentence reading comprehension skills in typically developing (TD) children and children with ID.…”
Section: Listening Comprehension and Visual-spatial Attention In Devementioning
confidence: 99%
See 3 more Smart Citations
“…Despite their achievements in word reading and comprehension (Jones et al, 2006;Lemons et al, 2013), most individuals with ID struggle to read and comprehend sentences (Fajardo, Ávila, Ferrer, Tavares, Gómez, & Hernández, 2014). Recently, van Wingerden et al (2016) evaluated the development of sentence reading comprehension skills in typically developing (TD) children and children with ID.…”
Section: Listening Comprehension and Visual-spatial Attention In Devementioning
confidence: 99%
“…Thus, it may be inappropriate for children with ID to receive repeated reading training with whole sentence units. Because these children are better at reading and segmenting words (Allor et al, 2010;Jones et al, 2006;Lemons et al, 2013;Ratz & Lenhard, 2013) than at reading sentences (Fajardo et al, 2014), a more successful strategy for their repeated reading training may be to present each word or segment in the sentence sequentially, one at a time.…”
Section: Repeated Reading Training With Whole Sentencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in a large state‐wide evaluation involving over 7,000 students who participated in one state's alternate assessment based on alternate academic achievement standards, Lemons et al. () showed that by 11th grade, very few students were able to read at the fifth‐grade level (2.6% of students with ID; 6.0% of students with ASD).…”
mentioning
confidence: 99%